System of Teaching Adjective Vocabulary in Elementary Grades (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
The linguistic basis of the methodology of working on word groups is the division of words into different groups according to their lexical-grammatical, morphological and syntactic features, that is, the science of word groups.